The Relationship Between e-Health Literacy and Breast Cancer Literacy Among Saudi Women - Alia Almoajel; Samar Alshamrani; Mesnad Alyabsi; Mesnad Alyabsi (Frontiers Media S.A., 2022)
Breast cancer is the most common cancer in women and represents a significant burden among women worldwide. The concept of health literacy is relatively new to the Gulf states, particularly to Saudi Arabia. Research on this topic is scarce, and no study has empirically explored the influence of e-health literacy on breast cancer literacy. The purpose of this study was to measure the impact of e-health literacy on breast cancer literacy among Saudi women in Riyadh city, Saudi Arabia. A cross-sectional survey was conducted online in a cohort of 336 women and disseminated via social media using the e-Health Literacy Scale (eHEALS) and Breast Cancer Literacy Assessment Tool (Breast-CLAT). Multiple regression analysis was executed to identify the sociodemographic factors that influence the e-health literacy and breast cancer literacy of participants. The participants showed high level of e-health literacy with total eHEALS score of 28.79, and better breast cancer literacy with total Breast-CLAT score of 23.44. This study yielded three significant findings: (1) e-health literacy is influenced by age and education which implies that youngest participants showed higher eHEALS scores than their older counterparts and that having increased education level reflected increased eHEALS scores, (2) breast cancer literacy is predicted by education and income which suggests that those who have higher levels of education and higher monthly incomes have increased levels of breast cancer literacy, and (3) breast cancer literacy and e-health literacy were associated which shows that participants with higher eHEALS scores were more likely have increased level of breast cancer literacy. The study revealed that the participants had high level of e-health literacy which correlated to their increased level of breast cancer literacy. The study findings implied that it is important for Saudi women to possess high levels of e-health literacy about breast cancer as more breast cancer educational resources are online nowadays.